Identitas Nasional Sebagai Alat Ketahanan Budaya di Era Globalisasi - Rahma, Velany Fadia (Maliki Interdisciplinary Journal, 2025)
National identity is the character of a nation-state that reflects the superiority and uniqueness distinguishing it from other nations. In the context of cultural resilience, national identity plays a crucial role as a safeguard against the tide of globalization, which brings various foreign cultural influences. This study aims to examine the role of national identity in maintaining Indonesia’s cultural resilience amid global challenges. The method used is a qualitative approach through a literature review of various relevant sources. The results of the study indicate that strengthening national identity through civic education, preservation of local culture, and the utilization of digital media or the internet can enhance public awareness of the importance of preserving one’s own culture. Furthermore, Pancasila, as the foundation of the state, functions as a filter against foreign values that do not align with the nation’s character and culture. Although challenges such as the influence of social media and the lack of understanding among younger generations regarding local culture persist, national identity remains a crucial element in safeguarding Indonesia’s cultural diversity